A retrospective observational study of people with Type 1 diabetes with self‐reported severe hypoglycaemia reveals high level of ambulance attendance but low levels of therapy change and specialist intervention1. Issue 9 (1st June 2018) - Field, B. C. T.; Nayar, R.; Kilvert, A.; Baxter, M.; Hickey, J.; Cummings, M.; Bain, S. C.
Abstract: Aim: To evaluate the impact of severe hypoglycaemia on NHS resources and overall glycaemic control in adults with Type 1 diabetes. Methods: An observational, retrospective study of adults (aged ≥ 18 years) with Type 1 diabetes reporting one or more episodes of severe hypoglycaemia during the preceding 24 months in 10 NHS hospital diabetes centres in England and Wales. The primary outcome was healthcare resource utilization associated with severe hypoglycaemia. Secondary outcomes included demographic and clinical characteristics, diabetes control and pathway of care. Results: Some 140 episodes of severe hypoglycaemia were reported by 85 people during the 2‐year observation period. Ambulances were called in 99 of 140 (71%) episodes and Accident and Emergency attendance occurred in 26 of 140 (19%) episodes, whereas 29 of 140 (21%) episode required no immediate help from healthcare providers. Participants attended a median of 5 (range 0–58) diabetes clinic consultations during the observation period; 13% (70 of 552) of all consultations were severe hypoglycaemia‐related. Of the HbA1c measurements recorded closest prior to severe hypoglycaemia ( n  = 119), only 7 of 119 measurements were < 48 mmol/mol (< 6.5%) and mean HbA1c was 70 (sd 19) mmol/mol (8.5%, sd 1.7%). Some 119 changes to diabetes treatment were recorded during the observation period (median/person 0;, range 0–11), of which 52 of 119 changes (44%) followed severe hypoglycaemic events. Conclusions: We observed a high level of ambulance service intervention but surprisingly low levels of hypoglycaemia follow‐up, therapy change and specialist intervention in people self‐reporting severe hypoglycaemia. These results suggest there may be important gaps in care pathways for people with Type 1 diabetes self‐reporting severe hypoglycaemia. What's new?: Some 71% of episodes of self‐reported severe hypoglycaemia involved ambulance call out. Only 13% of all diabetes clinic consultations were documented as hypoglycaemia follow‐up and at least 50% of people included in this study had no documented healthcare professional‐recommended changes to diabetes treatment. The results of our study suggest a lack of a consistent mechanism for reporting by paramedics to primary care and subsequent referral to specialist diabetes services, a lack of a consistent approach to early follow‐up by specialist diabetes services, and low levels of healthcare professional‐recommended therapy change and ongoing specialist review following self‐reported episodes of severe hypoglycaemia.